Analysis of Urban Morphology in Urban Settlement (Kuzguncuk Neighborhood) - Hiba Faez Kareem Al-Lami; Prof. Dr. Behiye Işik Aksulu; Asisst. Prof. Dr. Kerem Ercoşkun (Genius Journals, 2023)
The study of urban morphology between concept and application has an important role in the formation and knowledge of the development of cities and the stages of change that the city has undergone through different periods and the application of theoretical concepts that are interested in studying the urban morphology of the city, that urban morphology focuses on the studying of the processes of formation and transformation of the urban form based on its historical development, that is, different time stages will be chosen to study the region. With its contents of concepts such as urban form and theories of place, and thus aims to study the region and the factors that affected its urban form over different periods.
Keywords: Urban Morphology; Urban Fabric; Historical Settlement